Effect of overtime work on cognitive function in automotive workers - Proctor, Susan P; White, RF; Robins, TG; Echeverria, D; Rocskay, AZ (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVE ': 'The present investigation examined whether increased overtime work predicts impairment in cognitive performance in the domains of attention, executive function, and mood.' ' METHODS ': 'The behavioral and cognitive functions of 248 automotive workers were measured by a neurobehavioral test performance. Overtime, defined as number of hours worked greater than 8 h a day or greater than 5 d a week, was calculated from company payroll records for the week before the test day. The number of consecutive days worked before the test day was also determined.' ' RESULTS ': 'Cross-sectional data analysis by multiple linear regression, after adjustment for the effects of age, education, gender, alcohol intake, repeated grade in school, acute petroleum naphtha exposure, shift worked, job type, number of consecutive days worked before the test day, and number of hours worked on the test day before the testing, demonstrated that increased overtime was significantly associated with impaired performance on several tests of attention and executive function. Increased feelings of depression, fatigue, and confusion were also associated with increased overtime work. In addition significant interaction effects were observed for job type but not for naphtha exposure.' ' CONCLUSIONS ': 'The findings support the hypothesis that overtime work results in impaired cognitive performance in the areas of attention and executive function and that both overtime hours and the number of consecutive days worked prior to a test day affect mood.
Keywords: fatigue; machine-paced work; naphtha; neurobehavioral test; occupational health